Asia e University Holds its 8th Convocation - Borneo, Post (Borneo Post, 2018)
Asia e University (AeU) held its 8th convocations for 2662 graduands at Putra Wolrd Trade Centre (PWTC). The ceremony attended by families of the graduands from around of the world, representatives of foreign embassies from the 34 Asia Corporate Dialogue (ACD) countries and stakeholders.